MAINTAINING AND INHERITING DIALECTAL TRADITIONS THROUGH THE LENS OF LANGUAGE ECOLOGY - Hetilaniar; Dessy Wardiah (University of Kuningan, 2026)
This study investigates the challenges and strategies for preserving and passing down local dialects in South Sumatra, focusing on language ecology. Findings from interviews, field observations, and local document analysis reveal a significant decline in dialect usage, largely confined to informal family interactions, while Bahasa Indonesia and English dominate educational and professional contexts. Social and linguistic changes, influenced by urbanization and migration, further marginalize dialects. The study identifies several strategies for preserving dialects, including incorporating dialects into English as a Foreign Language (EFL) teaching, dialect digitization, media development, and community involvement. EFL teachers can use local dialects to teach English, integrating cultural elements such as folk tales to enhance students' language skills and promote linguistic diversity. Despite the challenges posed by globalization, these localized approaches can help maintain dialects in South Sumatra. The research provides valuable insights into the preservation of dialects in the region and offers practical implications for EFL education to support linguistic and cultural heritage.